The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1258/000456307780480828
|View full text |Cite
|
Sign up to set email alerts
|

The basis and management of metabolic abnormalities associated with cardiovascular risk in human immunodeficiency virus infection and its treatment

Abstract: This article was prepared at the invitation of the Clinical Sciences Review Committee of the Association for Clinical BiochemistryThe high global prevalence of human immunodeficiency virus (HIV) infection has been associated with high morbidity and mortality. The advent of highly active antiretroviral therapy (HAART) has, however, dramatically increased survival of patients infected with HIV. These patients now survive to develop metabolic complications of HIV infection and its treatment, including increased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…It is also involved in several essential CNS functions such as membrane trafficking, signal transduction, myelin formation, and synaptogenesis. [3][4][5] Lipid abnormalities are of longstanding clinical concern in treating HIV, 6 particularly hypocholesterolemia (HypoCHL), which is a prevalent comorbidity of HIV, even in the early stages. Compared to the general population, people living with HIV (PLWH) suffer a greater prevalence (40%)…”
Section: Introductionmentioning
confidence: 99%
“…It is also involved in several essential CNS functions such as membrane trafficking, signal transduction, myelin formation, and synaptogenesis. [3][4][5] Lipid abnormalities are of longstanding clinical concern in treating HIV, 6 particularly hypocholesterolemia (HypoCHL), which is a prevalent comorbidity of HIV, even in the early stages. Compared to the general population, people living with HIV (PLWH) suffer a greater prevalence (40%)…”
Section: Introductionmentioning
confidence: 99%
“…Different studies on lipid profiles in different countries show variations in their results. A study by Crook [ 34 ] showed that HIV infection is normally associated with hypocholesterolemia, hypertriglyceridemia, and low plasma HDLC levels. Another study by Pynka et al [ 35 ] showed that there was no significant difference in TC and LDL levels between HIV-infected and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The Data Collection on Adverse Events of Anti-HIV Drugs (D:A:D) study found that among HIV-infected individuals, even after adjustment for changes in lipids, there was increased risk of myocardial infarction with protease inhibitor (PI) use10. HIV-infection or cART may also change nontraditional or emerging risk factors for CHD, including inflammatory markers, clotting factors, apolipoproteins, lipoprotein (a), oxidative stress, non-esterified fatty acids, and homocysteine (Hcy)11.…”
Section: Introductionmentioning
confidence: 99%